Simulation and Analysis of Distributed Gateway System for First-Hop Redundancy (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Internet is expected to be available every time, so that the services run on it are able to be used any time. To achieve high availability Internet network, redundancy is used by employing more than one gateway so if one gateway is down, the other gateway will take the job of it. In the access layer, we use first-hop redundancy as the redundancy system. In this research, author design a system that has first-hop redundancy. The system is designed using software defined networking paradigm. The system uses POX as controller and Openflow as Controller Data-path Protocol Interface between switches and controller. The system is simulated on the mininet to examine the capability of the system by measuring some parameters: fail over delay, resource utilization and overhead on the bipartite topology. Of the examination results and analysis, the system is able to run the first-hop redundancy which yields fail-over delay below 140 ms for single flow.